ENT 530 Social Media Portfolio: a.shophaholicspes / Nur Zafirah Roslan - Roslan, Nur Zafirah (2020)
The a.shopaholicspes is a registered sole proprietor online business shop that conducted by Miss Nur Zafirah Binti Roslan. I started this business as it is rarely to see a plussize clothing shopping centre that could provide the same speciality in term of sizes and prices to the customers just like others clothing shops. I choose to help the curvy women to find the correct shopping centre for them. My shop stands with its mission and vision purposely to serve the community who are shopaholic specifically the curvy ladies to get the best shopping experience without any worries in term of prices, sizes or other common shopping problems faced by the customers. In this report, I will be discussed about my profile as the owner of a.shopaholicspes and my business information. I would also be describing the details of my business online shop’s mission and vision to give the clear picture of where stage would we bring our business to the community and how should we serve them. I used the type of teasers, hard sells, and soft sells as my marketing strategies to attract the potential customers. However, a.shopaholicspes shows its credibility through the registration to Go-eCommerce as a trusted seller in Malaysia. Next, the involvement of my product’s description would help my readers who also could be my potential customers to identify if any of my products specialty did fulfilling their demands so perhaps, they would be interested to know more about our plussize or curvy’s clothing attires. For example, the materials, price range and offered sizes from a.shopaholicspes.